2003
DOI: 10.1063/1.1604380
|View full text |Cite
|
Sign up to set email alerts
|

Locally preferred structure in simple atomic liquids

Abstract: We propose a method to determine the locally preferred structure of model liquids. This latter is obtained numerically as the global minimum of the effective energy surface of clusters formed by small numbers of particles embedded in a liquid-like environment. The effective energy is the sum of the intra-cluster interaction potential and of an external field that describes the influence of the embedding bulk liquid at a mean-field level. Doing so we minimize the surface effects present in isolated clusters wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
49
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 28 publications
(49 reference statements)
4
49
0
1
Order By: Relevance
“…36 The initial suggestion that the local order in simple liquids is not crystalline but icosahedral 36 (more generally polytetrahedral) has since been verified experimentally 37 and theoretically. 29,38 From the clusters viewpoint, the favored finite-size structures of good model glassformers have been shown by Doye and coworkers to be polytetrahedral.…”
mentioning
confidence: 99%
“…36 The initial suggestion that the local order in simple liquids is not crystalline but icosahedral 36 (more generally polytetrahedral) has since been verified experimentally 37 and theoretically. 29,38 From the clusters viewpoint, the favored finite-size structures of good model glassformers have been shown by Doye and coworkers to be polytetrahedral.…”
mentioning
confidence: 99%
“…This statement would be valid even in the bulk liquids or glasses as Mossa and Tarjus [17] showed that the liquid-like disordered environment only slightly affects the stability of isolated clusters.…”
Section: Numerical Results and Discussionmentioning
confidence: 97%
“…Instead, we use the LJ system considered by Kob and Andersen [14] which was shown to form a bulk glass, and use more efficient modified space-fixed genetic algorithm developed by the author [15] in this work. Although the stability of a cluster in liquid or BMG and in free space would be different, Mossa and Tarjus [17] found that the liquid-like disordered environment only slightly affects the stability of the cluster. The stability of an isolated cluster would be a good indication of the stability of a similar cluster in undercooled liquids or glasses.…”
Section: Introductionmentioning
confidence: 99%
“…Since a large portion of the bonding energy (up to ~40%) is usually contributed from the first neighbor interactions, including the interactions from the remote neighbors may not change the scenario qualitatively. Indeed, as shown in recent work [28,29] including these interactions explicitly only adds minor changes in the cluster energy. Now we are ready to discuss the next question: How the clusters form.…”
mentioning
confidence: 87%